Novel Three-state Quantum Dot Gate Field Effect Transistor Fabrication, Modeling and Applications - Karmakar, Supriya; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2014)
The book presents the fabrication and circuit modeling of quantum dot gate field effect transistor (QDGFET) and quantum dot gate NMOS inverter (QDNMOS inverter). It also introduces the development of a circuit model of QDGFET based on Berkley Short Channel IGFET model (BSIM). Different ternary logic circuits based on QDGFET are also investigated in this book. Advanced circuit such as three-bit and six bit analog-to-digital converter (ADC) and digital-to-analog converter (DAC) were also simulated.
Introduction: Multi State Devices and Logic -- Quantum Dot Gate Field Effect Transistor Device Structures -- Quantum Dot Gate Field Effect Transistors Fabrication and Characterization -- Quantum DOT Gate Field Effect Transistors Theory and Device Modeling -- Quantum Dot Gate NMOS Inverter -- Quantum Dot Gate Field Effect Transistor (QDGFET): Circuit Model and Ternary Logic Inverter -- Analog-to-Digital Converter (ADC) and Digital-to-Analog Converter (DAC) Using Quantum DOT Gate Field Effect Transistor (QDGFET) -- Performance in SUB-25nm Range -- Conclusions.
Keywords: Engineering; Systems engineering; Engineering; Nanotechnology and Microengineering; Circuits and Systems; Electronic Circuits and Devices